Спецификация: история и реальность - Sorokin, Artom (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the notion of specification in the law system of the Russian Federation. Presenting this term the author focus on both historical and contemporary perspective.